1995
DOI: 10.1071/bt9950223
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Lomandra sonderi (Dasypogonaceae) Promoted by Pericarp Removal and Chemical-Stimulation of the Embryo

Abstract: Lomandra Labill. is a common genus in the understorey of the jarrah (Eucalyptus marginata Sm.) forest of Western Australia. Species in this genus are difficult to propagate by seed and do not readily reestablish following mining. Limiting factors for germination success were explored and identified. Lomandra sonderii (F.Muel1.) Ewart set very few seed (seeds per flower = 0.122). Tetrazolium tests indicated that seed viability was relatively high (50%). Germination was inhibited (0%) by the inner pericarp tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 17 publications
0
26
0
1
Order By: Relevance
“…Fruit or seed coats may restrict oxygen and water exchange, and may create a physical barrier to radicle emergence (Beardsell et al 1993). Inhibitors may also be present in the seed coat, pericarp, endosperm or embryo itself and prevent germination of seed (Richmond & Chinnock 1994; Richmond & Ghisalberti 1994; Plummer et al 1995). Although some fleshy‐fruited species require leaching of the seed to wash away inhibitors and stimulate germination (Bell et al 1993), the detachment of the seed coat from the endosperm and embryo may also remove inhibitors allowing germination to proceed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fruit or seed coats may restrict oxygen and water exchange, and may create a physical barrier to radicle emergence (Beardsell et al 1993). Inhibitors may also be present in the seed coat, pericarp, endosperm or embryo itself and prevent germination of seed (Richmond & Chinnock 1994; Richmond & Ghisalberti 1994; Plummer et al 1995). Although some fleshy‐fruited species require leaching of the seed to wash away inhibitors and stimulate germination (Bell et al 1993), the detachment of the seed coat from the endosperm and embryo may also remove inhibitors allowing germination to proceed.…”
Section: Discussionmentioning
confidence: 99%
“…In large‐seeded species, however, light exposure may reduce maximum percentage germination under higher temperatures, but at 15°C this temperature/light interaction has minimal effect on germination percentages (Bell et al 1995). Light effects may be overcome under laboratory conditions with the application of the growth hormone gibberellic acid (Bell et al 1993, 1995; Plummer et al 1995).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most myrmecochores occur in the temperate sclerophyll forest and heath/shrubland in the south (Berg 1975) where they comprise 30-50% of the species in some communities (Willson et al 1990). Benefits to the seeds can include increased dispersal distance (Andersen 1988;Whitney 2002), scarification (Plummer et al 1995) or protection from fire (Auld 1986). The fate of seeds is largely dependent on the attributes of the dispersing ants (Hughes & Westoby 1992).…”
Section: Seed Dispersingmentioning
confidence: 99%
“…Tissue cultures of dryland rush and sedge species are initiated from extracted embryos using modifications of Meney’s methods (Meney 1993; Meney & Dixon 1995). For Lomandra species of the Dasypogonaceae, seed numbers are sufficient for tissue culture initiation by modification of Crawford’s in vitro method (Plummer et al 1995). For many species, early work found that transfer from the laboratory to the greenhouses had poor plant survival, until ventilation of the culture vessels was introduced by modification of Rosetto’s method (Rossetto et al 1992).…”
Section: Sources Of Plantsmentioning
confidence: 99%